2018
DOI: 10.1590/1983-1447.2018.20180119
|View full text |Cite
|
Sign up to set email alerts
|

Care transition strategies in Latin American countries: an integrative review

Abstract: OBJECTIVE To identify and analyze available literature on care transition strategies in Latin American countries. METHODS Integrative literature review that included studies indexed in PubMed, LILACS, Web of Science Core Collection, CINAHL, SCOPUS databases, and the Scientific Electronic Library Online (SciELO), published in Portuguese, Spanish or English, between 2010 and 2017. RESULTS Eleven articles were selected and the strategies were grouped into components of care transition: discharge planning, advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
34

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 29 publications
0
50
0
34
Order By: Relevance
“…Entretanto, os enfermeiros têm uma boa comunicação com os pacientes e familiares de modo que conhecem o contexto familiar e a rede de apoio. Ainda sobre o preparo para a alta, um estudo destacou a relevância dos enfermeiros envolverem os familiares no cuidado durante a internação com vistas aos cuidados adequados no domicílio 21 . O envolvimento da família nas intervenções recomendadas para o pós-alta hospitalar garante o sucesso do plano de cuidados e da continuidade do cuidado no domicílio 19 .…”
Section: Competências Para a Continuidade Do Cuidadounclassified
See 1 more Smart Citation
“…Entretanto, os enfermeiros têm uma boa comunicação com os pacientes e familiares de modo que conhecem o contexto familiar e a rede de apoio. Ainda sobre o preparo para a alta, um estudo destacou a relevância dos enfermeiros envolverem os familiares no cuidado durante a internação com vistas aos cuidados adequados no domicílio 21 . O envolvimento da família nas intervenções recomendadas para o pós-alta hospitalar garante o sucesso do plano de cuidados e da continuidade do cuidado no domicílio 19 .…”
Section: Competências Para a Continuidade Do Cuidadounclassified
“…O compartilhamento de informações entre os serviços é essencial para promover a continuidade do cuidado e garantir que os profissionais da APS tenham conhecimento dos pacientes submetidos à internação hospitalar. Essa comunicação pode ser realizada por meio de e-mails, telefonemas, relatórios de alta detalhado e sistema informatizado integrado 21 . No pós-alta, o acompanhamento por contato telefônico, visitas domiciliares ou serviços de assistência domiciliar são importantes para identificar e prover recursos mais adequados 18 à continuidade do cuidado.…”
Section: Competências Para a Continuidade Do Cuidadounclassified
“…Cancer patient's hospital discharge requires commitment from the team, patient and family. CT is being considered an important strategy to contribute to continuity of care, reducing the number of hospital admissions, as well as impacting the decrease in readmissions caused by complications [4]. Furthermore, this strategy may reduce the cost of health services, contribute to more effective treatment of patients, the longevity of people with comorbidities and improve the quality of life for patients and their families [5][6][7][8].…”
Section: Objectivementioning
confidence: 99%
“…The care transition process is de ned as a set of coordinated actions for continuous patient care from the moment of admission to hospital discharge, as well as the transfer of patients between units in the same facility or between different health services [3]. These actions include discharge planning, health education for the patient and family, promotion of self-management of care, guidance on medications, coordination between health services, communication between teams and post-discharge monitoring [4,5]. For an effective and safe care transition, it is necessary to overcome the organizational barriers of the different levels of health care, establishing the appropriate coordination mechanisms and rede ning, if necessary, the functions within interprofessional teams [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies [7,8] have shown that the lack of planning and preparation for discharge, the di culty in selfmanagement of medications, the occurrence of adverse events and the increase in readmissions are common. On the other hand, effective care transitions were associated with cost reduction in health services, hospital readmissions and improvement in patients' quality of life [4,5].…”
Section: Introductionmentioning
confidence: 99%